2023
DOI: 10.1155/2023/9349494
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Pan‐Cancer Analysis of Prognostic and Immune Infiltrates for the TMEM65, Especially for the Breast Cancer

Abstract: Introduction. Transmembrane protein 65 (TMEM65) is an inner mitochondrial membrane protein, which played important role in mediating autophagy, smooth muscle contraction, protein glycosylation, and immune response. In recent years, the interest had risen for exploring the function of the TMEM genes in the cancer fields. As a consequence, in our pan-cancer research of the TMEM65, we explored the function of the gene in kinds of database and tried to apply the finding in the clinical practice. Methods. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 31 This study focused on the roles of ferroptosis and pyroptosis in BC and analysed the relationship between ferroptosis and immune infiltration. Other researchers have carried out Transmembrane protein 65 (TMEM65) pan‐cancer studies, and the results found TMEM65 to be associated with certain pathways (TGF beta signalling, TNFA signalling, hypoxia, pyroptosis, 32 DNA repairing, autophagy, ferroptosis, ferroptosis and ferroptosis) in BC. In contrast, this study focuses on TMEM65 and confirms the role of ferroptosis and pyroptosis in BC from a different perspective.…”
Section: Discussionmentioning
confidence: 99%
“… 31 This study focused on the roles of ferroptosis and pyroptosis in BC and analysed the relationship between ferroptosis and immune infiltration. Other researchers have carried out Transmembrane protein 65 (TMEM65) pan‐cancer studies, and the results found TMEM65 to be associated with certain pathways (TGF beta signalling, TNFA signalling, hypoxia, pyroptosis, 32 DNA repairing, autophagy, ferroptosis, ferroptosis and ferroptosis) in BC. In contrast, this study focuses on TMEM65 and confirms the role of ferroptosis and pyroptosis in BC from a different perspective.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%